2017
DOI: 10.22159/ijpps.2017v9i6.14221
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of a Novel Mucoadhesive Derivative of Psyllium Seed Polysaccharide

Abstract: Objective: In the present study, thiol-functionalization of psyllium seed polysaccharide (PSY) was cross-linked with thioglycolic acid by esterification in an attempt to reveal the mucoadhesive properties of thiolated psyllium seed polysaccharide (TPSY). Methods:The crosslinking was carried out by the microwave-assisted method. A simplex centroid design was employed to systematically study the mucoadhesive strength, mucoadhesive retention time and drug release profile. Comparative evaluation of carbopol-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…1). Psyllium fibre showed a broad peak at 2θ of 19.7° of less intensity (Bajpai et al ., 2015; Rao et al ., 2017; Kumar et al ., 2019). The evident halo pattern in the diffractograms was indicative of the amorphous nature of psyllium.…”
Section: Resultsmentioning
confidence: 99%
“…1). Psyllium fibre showed a broad peak at 2θ of 19.7° of less intensity (Bajpai et al ., 2015; Rao et al ., 2017; Kumar et al ., 2019). The evident halo pattern in the diffractograms was indicative of the amorphous nature of psyllium.…”
Section: Resultsmentioning
confidence: 99%
“…21) showed a change in surface morphology after grafting. The more roughness and unevenness on the surface of grafted gum due to the deposition of acrylamide was clearly visible [26,27].…”
Section: Selection Of Optimized Batchmentioning
confidence: 98%
“…18b). The change in surface morphology was clearly revealed by scanning electron micrographs, which showed that more unevenness and roughness due to the deposition of acrylamide on the surface of karaya gum [32][33][34][35].…”
Section: Morphologymentioning
confidence: 99%